2003
DOI: 10.1161/01.cir.0000099507.32936.c0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins on Platelet Inhibition by a High Loading Dose of Clopidogrel

Abstract: Background-Recent studies suggested that some HMG-CoA reductase blockers might inhibit the antiplatelet activity of clopidogrel. Therefore, we analyzed how various statins together with a high loading dose of clopidogrel (600 mg) affect platelet aggregation. Methods and Results-Seventy-seven patients with stable angina scheduled for elective coronary stenting were studied.Patients were randomized to receive atorvastatin, fluvastatin, lovastatin, pravastatin, simvastatin (each 20 mg), cerivastatin (0.3 mg), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(39 citation statements)
references
References 16 publications
4
33
0
1
Order By: Relevance
“…Therefore, there has been considerable speculation and concern that potentially significant drug-drug interactions may occur when these two medications are co-administered. [2][3][4][5] A number of in vitro and in vivo studies have been conducted to determine the potential for the interactions with the primary focus upon the effect of simvastatin-mediated CYP3A inhibition on the activation of clopidogrel. 7,9,10) However, these studies have often led to inconsistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has been considerable speculation and concern that potentially significant drug-drug interactions may occur when these two medications are co-administered. [2][3][4][5] A number of in vitro and in vivo studies have been conducted to determine the potential for the interactions with the primary focus upon the effect of simvastatin-mediated CYP3A inhibition on the activation of clopidogrel. 7,9,10) However, these studies have often led to inconsistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the active metabolite simvastatin acid is further metabolized by CYP3A4, with less contribution from CYP3A5, CYP2C8 and uridine 5′-diphosphate (UDP) glucuronosyltransferase. 5) It has been suspected that the activation and antiplatelet effect of clopidogrel could be attenuated under conditions of co-administration with certain statins, such as simvastatin, since CYP3A4 is involved in the metabolism of both compounds and simvastatin is a potent CYP3A4 inhibitor. 5,6) Some in vitro and ex vivo studies showed that simvastatin significantly impaired the biotransformation and antiplatelet activity of clopidogrel via inhibition of CYP3A4 7,8) (Fig.…”
mentioning
confidence: 99%
“…Secondly, 5 studies (Serebruany et al 2001;Müller et al 2003;Saw et al 2003;Wienbergen et al 2003;Mitsios et al 2004) were not able to demonstrate any interaction between clopidogrel and statins. However, in 2 (Serebruany et al 2001;Wienbergen et al 2003) of those 5 studies, the patients were not categorized in ''patients recieving CYP3A4 metabolized statins'' versus ''patients receiving other statins''.…”
Section: Important Bias Potentially Affecting Interpretation!mentioning
confidence: 95%
“…First of all, only Müller et al (2003) based their sample size on a power calculation. Consequently, an insufficient sample size could easily be an important issue affecting the results obtained in the remaining trials.…”
Section: Important Bias Potentially Affecting Interpretation!mentioning
confidence: 99%
See 1 more Smart Citation